Scrutinizing the value and implementation of volitional personality development at work - Marie Hennecke; Pia V. Ingold (International Journal of Selection and Assessment, 2024)
Abstract In this commentary, we discuss Dupré and Wille's proposal (2024) to consider employees' personality change goals in the work context. We compare volitional personality development to skill development and call for more evidence to determine the benefits for both employees and organizations in this context. We also put forward that a clearer understanding is required of how job demands influence personality traits and of how these demands interact with and shape the integration of potential complementary personality development training modules. In closing, we provide avenues for future research.
Keywords: 330; development; development goals; job demands; personality; personality assessment; personality development; personnel; volition; volitional personality development